Success after tenure : supporting mid-career faculty - Baker, Vicki L., 1978-; Neisler, Gretchen; Lunsford, Laura Gail; Pifer, Meghan J., 1978-; Terosky, Aimee LaPointe (Stylus Publishing LLC, 2019)
"This book brings together leading practitioners and scholars engaged in professional development programming for and research on mid-career faculty members. The chapters focus on key areas of career development and advancement that can enhance both individual growth and institutional change to better support mid-career faculties. The mid-career stage is the longest segment of the faculty career and it contains the largest cohort of faculty. Also, mid-career faculty are tasked with being the next generation of faculty leaders and mentors on their respective campuses, with little to no supports to do so effectively, at a time when higher education continues to face unprecedented challenges while managing the continued goal of diversifying both the student and faculty bodies"--